1374. Carbapenem-Resistant Enterobacterales Infection in Children: Clinical and Molecular Data from a Prospective Multicenter Cohort Study. (31st December 2020) - Fisher, Matthew; Dai, Weixiao; Doi, Yohei; Doi, Yohei; Komarow, Lauren; Patel, Gopi; Revolinski, Sara; Huskins, W Charles; Fries, Bettina C; Banerjee, Ritu; Banerjee, Ritu
Abstract: Background: Carbapenem Resistant Enterobacterales (CRE) are an urgent public health threat. We describe the clinical and molecular epidemiology of CRE infection in a multicenter pediatric cohort. Methods: Patients under 18 years of age with CRE positive cultures between April 30 2016 and August 31 2017 were identified from among 49 hospitals participating in the Consortium on Resistance Against Carbapenems in Klebsiella and Other Enterobacteriaceae. Isolates representing colonization or infection were included. Bacterial identification and antimicrobial susceptibility testing were performed in each contributing clinical microbiology laboratory. Carbapenem resistance was defined per CDC criteria as those isolates displaying imipenem, doripenem, or meropenem MIC ≥4 μg/mL or ertapenem MIC ≥2 μg/mL. Clinical and epidemiological data were obtained from the electronic health record. Carbapenemase genes were detected using PCR. Results: 51 pediatric patients with CRE were identified at 17 hospitals. All regions of the United States were represented, with highest prevalence in the South (46%), followed by the Northeast (24%), Midwest (20%) and West (10%). The mean age at time of positive culture was 4 years. 66% of children were under age 2. 53% were male. 40% were white, 38% black, and 18% Hispanic. Mean time from admission to culture was 25 days. 72% of children were in an ICU at the time of culture, including 18% in the neonatal ICU. 42% required mechanical ventilation prior to culture. History of malignancy was present in 14% of children. The most common source was urine (31%), followed by respiratory (25%), and blood (18%). The most common species were Enterobacter cloacae (29%), Klebsiella pneumoniae (24%) and E. coli (20%). Carbapenemase genes were detected in 8 out of 35 (23%) isolates tested. 90-day mortality was 18%. Mortality was highest for K. pneumoniae (42%). The majority of subjects (88%) did not receive effective antibiotic therapy on the day of culture collection. Table 1 Table 2 Conclusion: CRE infection or colonization in children in the U.S. was geographically widespread, likely hospital-acquired, and associated with high mortality. A significant portion of patients were infants. Ineffective antibiotic therapy was common at illness onset. Disclosures: W. Charles Huskins, MD, MSc, ADMA Biologics (Consultant)Pfizer, Inc (Consultant)